The Mechanism of Legal Regulation in the Conditions of Globalization and Formation of Information Environment. Regional Aspect - AVDEEV, Vadim Avdeevich; AVDEEVA, Olga Anatolievna; SHAGIEVA, Rozalina Vasilevna; SMIRNOVA, Vera Vladimirovna; MASHKIN, Nikolay Afanasievich; TARADONOV, Sergey Valerievich (Journal of Environmental Management and Tourism; Vol 10 No 7 (2019): JEMT Volume X Issue 7(39) Winter 2019DO - 10.14505//jemt.v10.7(39).09, 2020)
The article deals with topical issues of legal regulation of processes related to cyberspace and the informatization of society. The problems that have arisen are due to the need to ensure the inviolability of computer information, the operation of the system or networks precluding harm to a person, society or the state. The development of the information space inevitably has a negative impact on the rights of every person encroaching on privacy. International instruments are aimed at implementing measures to ensure the inadmissibility of the collection, storage, use and dissemination of information about the private life of a person without his consent. Regulation of cyberspace in the context of legal informatization actualizes the acceptance of measures at the regional level to be fixed in legislative acts. Improvement of technological means of information protection is required. The development of information technology entails the active use of legal measures of influence. These measures should be aimed at protecting the state system, the country's defense, state security, morality and public health. The main objectives of the regulation of information and legal space are recognized information and legal support of the state bodies, legal entities and individuals and the preservation of the information legal field. The legislator at the regional level develops measures of counteraction. Legal measures play a key role in the regulation of information and legal space.